Metode Storytelling dalam Membina Perilaku Religius Siswa Sekolah Dasar YP Indra Palembang - Holidi, Holidi; Karoma, Karoma; Astrid, Annisa (Al-Fikru: Jurnal Ilmiah, 2021)
This study aims to analyze the application of the storytelling method in fostering students' religious behavior and the factors supporting and inhibiting the application of storytelling in fostering students' religious behavior. The research method used is descriptive qualitative. Methods of data collection using observation, interviews, and documentation studies. Research informants in this case are teachers of Islamic Religious Education and students of SD YP Indra Palembang. Data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the research are the application of the storytelling method embodied in Islamic stories such as the stories of the Prophets and Apostles, friends, scholars, and pious people both sourced from the Qur'an, Hadith, or the books of the scholars. Its implementation is carried out through the stages of planning, implementation, and evaluation. The application of the method as well as in the context of inculcating the values ​​of faith, worship, morals, psychology. The inhibiting factor is the lack of learning media, lack of teaching skills. The supporting factor is the existence of school policies to make the presentation of subject matter easier and more enjoyable.